2015
DOI: 10.1002/elan.201500486
|View full text |Cite
|
Sign up to set email alerts
|

A Galactose Oxidase Biosensor Based on Graphene Composite Film for the Determination of Galactose and Dihydroxyacetone

Abstract: A novel amperometric biosensor was developed by immobilizing galactose oxidase (GAox) on poly (L‐lactide) stabilized gold nanoparticles (Au@PLLA) modified graphene nano‐composite film (RGO‐Au@PLLA/GAox). The direct electron transfer (DET) of GAox was achieved. Cyclic voltammetry of the GAox in the RGO‐Au@PLLA film revealed a pair of well‐defined and quasireversible peaks at about −0.137 V (vs. SCE), which is characterized of the Cu(II)/Cu(I) redox couple for the galactose oxidase. Amperometric response was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…When the enzyme was immobilized directly on the ITO surface, the response towards galactose showed a quasi-reversible redox pair formed by a cathodic wave at −125 mV due to the reduction of the Cu present in the coenzyme, from Cu(II) to Cu(I), that accompanied the oxidation of galactose. The anodic wave at 150 mV was also observed due to the oxidation from Cu(I) to Cu(II) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the enzyme was immobilized directly on the ITO surface, the response towards galactose showed a quasi-reversible redox pair formed by a cathodic wave at −125 mV due to the reduction of the Cu present in the coenzyme, from Cu(II) to Cu(I), that accompanied the oxidation of galactose. The anodic wave at 150 mV was also observed due to the oxidation from Cu(I) to Cu(II) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…GAO is able to oxidize D-galactose, giving the corresponding aldehyde (D-galactohexodialdose) accompanied by the reduction of O 2 to H 2 O 2 . The activity of GAO can be improved by using an appropriate matrix and a suitable electron mediator [ 20 , 21 , 22 ]. Phthalocyanines have been demonstrated to be efficient electron mediators, and CHI can be an ideal support for enzyme immobilization through the amino groups.…”
Section: Introductionmentioning
confidence: 99%
“…Further we compared published GaOx based systems with our proposed system based on PyOx‐MTs, acceptable and comparable results were found (Table ). For example Tkac et al., in their study suggested single walled carbon nanotubes dispersed in a chitosan matrix using GaOx for the design of a galactose biosensor .…”
Section: Resultsmentioning
confidence: 99%
“…An easier, more accurate, and quantifiable measure of galactose could improve screening as well as monitoring. While some prior work on galactose biosensing is present in the literature [23,24,25,26,27,28,29,30,31], the number of reports is limited when compared to highly targeted species such as glucose. Prior work has also focused on the detection of galactose through gas/liquid chromatography, or electrochemical strategies requiring redox mediators (i.e., 2nd generation schemes) or the covalent attachment of galactose oxidase (GaOx) to a surface [26,29,32].…”
Section: Introductionmentioning
confidence: 99%